Fatal pursuit : a Bruno, chief of police novel - Walker, Martin, 1947 January 23- (Walker, Martin, 1947 January 23- Bruno series., 2016)
A pair of murders, a little romance, and rivals in pursuit of a long-lost vintage car of unfathomable value--Bruno, chief of police, is busy in another mystery set in the beautiful Dordogne.